2020
DOI: 10.1590/1678-4324-2020190222
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics, Therapeutic Uses, and Legal Aspects of the Cannabinoids of Cannabis sativa: A Review

Abstract: Marijuana (Cannabis sativa) is an important annual medicinal plant that belongs to the Cannabaceae family. It contains 421 substances of 18 chemical types-the most significant compound is δ-9-tetrahydrocannabinol, which causes several effects, both in the Central Nervous System and in several peripheral locations in the organism. The objectives of this scientific review are to mention the anatomical distribution, chemical characteristics and biosynthesis of cannabinoids, as well as its actions mechanisms. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 68 publications
0
16
0
1
Order By: Relevance
“…Atualmente, a utilização da C. sativa tem se mostrado bastante eficaz no tratamento de diversas patologias, a partir de diferentes formas de administração associada ao consumo de derivados da planta. Os efeitos terapêuticos estão fortemente correlacionados a ativação do sistema endocanabinóide, que implica na regulação de diversas funções fisiológicas, como: metabolismo, inflamação, comportamento alimentar, sistema imune, funções cognitivas, ciclo do sono e modulação hormonal (BARRALES-CUREÑO et al, 2020;DALCIN, 2019).…”
Section: Discussionunclassified
“…Atualmente, a utilização da C. sativa tem se mostrado bastante eficaz no tratamento de diversas patologias, a partir de diferentes formas de administração associada ao consumo de derivados da planta. Os efeitos terapêuticos estão fortemente correlacionados a ativação do sistema endocanabinóide, que implica na regulação de diversas funções fisiológicas, como: metabolismo, inflamação, comportamento alimentar, sistema imune, funções cognitivas, ciclo do sono e modulação hormonal (BARRALES-CUREÑO et al, 2020;DALCIN, 2019).…”
Section: Discussionunclassified
“…These compounds have proven therapeutic effect against pain, depression, anxiety, arthritis, musculoskeletal diseases, etc. and also have anticancer, antiemetic, antiglaucoma and psychotic properties [12,22]. Experimental studies have shown that activation of cannabinoid receptors, triggered by cannabinoids, results in antitumourgenic activity in most cases that specifically inhibits tumour cell proliferation and/or blocks tumour invasion/metastasis [23][24][25][26].…”
Section: Therapeutic Uses Of Cannabis Sativamentioning
confidence: 99%
“…Experimental studies have shown that activation of cannabinoid receptors, triggered by cannabinoids, results in antitumourgenic activity in most cases that specifically inhibits tumour cell proliferation and/or blocks tumour invasion/metastasis [23][24][25][26]. In addition, cannabinoids are capable of inducing cell apoptosis [22]. Therefore, cannabinoids act as potent anticancer agents against various cancer cell lines such as lymphomas, gliomas, lung cancer, thyroid epithelioma, breast cancer colon cancers and prostate cancers [27][28][29][30][31][32][33].…”
Section: Therapeutic Uses Of Cannabis Sativamentioning
confidence: 99%
“…The method was also evaluated for screening of seven other cannabinoids namely CBN, cannabichromene (CBC), cannabicitran (CBT), delta-8-tetrahydrocannabinol (Δ8-THC), tetrahydrocannabivarin (THCV), cannabidivarin (CBDV) and cannabigerol (CBG). These cannabinoids were selected based on their biosynthesis pathway [9,10] and their medical and pharmaceutical interest [11,12].…”
Section: Introductionmentioning
confidence: 99%